2019
DOI: 10.3390/ijerph17010212
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Disparities among Migrant Children at School Entry in Germany. How does the Definition of Migration Status Matter?

Abstract: Background: Migration background is known to be an important risk factor for a number of medical outcomes. Still, relatively little is known about the epidemiologic relevance of different definitions of migration status. Methods: Data from 5250 school entry examinations spanning three consecutive years (2015–2017) were gathered from the Public Health Department in Halle, Germany. Data were stratified according to six different migration statuses and evaluated for differences in health service utilization and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…This insight is not possible when using a binary indicator for migration background. The few previous studies accounting for this factor have confirmed that people with a onesided migration background and non-migrants are similar with respect to their health care utilization [16,39].…”
Section: Discussionmentioning
confidence: 84%
“…This insight is not possible when using a binary indicator for migration background. The few previous studies accounting for this factor have confirmed that people with a onesided migration background and non-migrants are similar with respect to their health care utilization [16,39].…”
Section: Discussionmentioning
confidence: 84%
“…In the current study, the physical HrQoL was positively associated with the oral ability in the German language. As oral ability might be an informal facilitator to accessing health care, it might thereby also have an influence on HrQoL ( 29 , 46 , 47 ). A worse ability in the German language of parents with direct migration background was directly negatively associated with the mental health of their children ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Migrant-specific demographic factors, including generation, race or ethnicity, and duration at a specific destination, were associated with immigrants' and IMs' HSU. First-generation immigrants (64,(107)(108)(109) and old-generation IMs (50) had worse HSU than the others because the early generation had more barriers to becoming integrated into society. The home country of the immigrants, including Asia or developing countries (88- 91,110,111), and nationality (112) of IMs were found to be associated with HSU.…”
Section: Predisposing Factorsmentioning
confidence: 99%